1996
DOI: 10.1084/jem.184.4.1585
|View full text |Cite
|
Sign up to set email alerts
|

A p70 killer cell inhibitory receptor specific for several HLA-B allotypes discriminates among peptides bound to HLA-B*2705.

Abstract: Natural killer (NK) cells express a repertoire of killer cell inhibitory receptors (KIR) for major histocompatibility complex (MHC) class I molecules. KIR specificity for MHC class I can be broad, as in the case of a single p70 KIR that can recognize several HLA-B allotypes, including HLA-B*2705. On the other hand, recognition of MHC class I can also be highly specific, as in the case of NK clones that recognize HLA-B*2705 in a peptide-specific manner. Most NK cells express multiple KIR sequences. To determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 24 publications
6
95
0
Order By: Relevance
“…Such peptides may be produced in response to infection and introduce allosteric changes in HLA-C molecules or enhance the binding of HLA-C molecules by their cognate KIR receptor. Indeed, KIR preference for certain peptides sequences has been previously demonstrated in studies examining NK cell recognition of HLA-B27-expressing target cells (61,62) and in KIR2DL recognition of HLA-C molecules (63,64). However, we consider it unlikely that differential peptide recognition explains the better NK cell response conferred by the KIR2DL3/HLA-C1 compound genotype compared with the KIR2DL1/HLA-C2 compound genotype for the following reasons.…”
Section: Hla-c1 Homozygous and Hla-c2 Homozygous Groups Appearedmentioning
confidence: 69%
“…Such peptides may be produced in response to infection and introduce allosteric changes in HLA-C molecules or enhance the binding of HLA-C molecules by their cognate KIR receptor. Indeed, KIR preference for certain peptides sequences has been previously demonstrated in studies examining NK cell recognition of HLA-B27-expressing target cells (61,62) and in KIR2DL recognition of HLA-C molecules (63,64). However, we consider it unlikely that differential peptide recognition explains the better NK cell response conferred by the KIR2DL3/HLA-C1 compound genotype compared with the KIR2DL1/HLA-C2 compound genotype for the following reasons.…”
Section: Hla-c1 Homozygous and Hla-c2 Homozygous Groups Appearedmentioning
confidence: 69%
“…On the other hand, it has been reported that binding of KIR is dependent on peptide as well as the class I molecule on the target cell. 26,34,35 Conformational changes in class I molecules after binding of certain peptides may influence its KIR binding specificity, and it may be an explanation for the association of only B*2702 with Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that KIR3DL1 binds the MHC a1 helix around residues 76-80, with specificity for all Bw4 alleles containing threonine at heavy-chain residue 80 [17]. In the case of HLA-B*2705 at least, KIR3DL1 also has specificity for bound peptide, showing greatest sensitivity for the residue at position 8 [18][19][20].…”
Section: Introductionmentioning
confidence: 99%